Thermal and Chemical Analysis of Waste Modified Bitumen - Hosein Zanjirani farahani; Massoud Palassi; Javad Nemati (پژوهش‌های زیرساخت‌های عمرانی, 2019)
In this paper, the thermal analysis of modified bitumen by us-ing recycled and waste crumb rubber has been investigated. At first, thermal conductivity analysis of materials has been investigated with increasing temperature, and the most im-portant thermal analysis experiments, such as thermo-gravimetric analysis (TGA) and differential scanning calorim-etry (DSC) have been performed on samples. It has been ob-served that modified bitumen with recycled plastics perform better in terms of thermal analysis characteristics. Finally, FTIR analysis was performed to determine the structure of the compounds on the bitumen. and plastics were recycled and found that by modification of bitumen with recycled plastics a chemical reaction does not occur.